Postdocs and the Internationalization of Academic Labor - Cantwell, Brendan (International Higher Education, 2012)
The postdoctorate appears to have internationalized more rapidly and to a greater extent than other categories of academic work. There are several interrelated factors that can explain this trend, which presents both challenges and opportunities.